Long-run dynamic relationship between FDI and domestic investment in GCC countries - Hassan B. Ghassan; Hassan R. Alhajhoj (Economics and Econometrics Research Institute (EERI), 2016)
The paper aims to examine the relationship, whether complementary or substitutive, between inward FDI and gross domestic investment in the six GCC countries using cointegration techniques and fully modified GMM estimation. Based on the panel data, the empirical evidence implies that in Qatar, Oman, the UAE and Saudi Arabia, the inward FDI has positive short-run and long-run effects on the domestic investment. For Bahrain, such a complementary relationship exists only in the short-run. For the majority of GCC countries, the long-run elasticities have large magnitude compared to the short-run counterparts, justifying more attraction policy of the IFDI in the future. The gap in the privatization process of public enterprises in the GCC explains in a large extent their heterogeneity in terms of elasticities and spillovers effects.
Keywords: F2; C5; 330; FDI; Domestic investment; GMM; Long-run Elasticities; GCC